Massive Open Online Courses as a Tool for Developing Future Teachers’ Digital Competence (Journal of Educational Sciences, 2020)
Today there is a growing demand for Massive open online courses (MOOCs) on distance learning in higher education. Massive open online courses play a significant role in open, continuous, lifelong learning as a new trend and a new distance learning technology in education. There exist many opportunities to develop future pedagogues’ digital competence by creating and applying Massive open online courses. The research briefly summarizes the theory of development and application of a Massive open online course based on the analysis of foreign literature. Based on this, an elective course is offered to create a mass open online course. Before applying the MOOC, a survey was conducted for students of 1-4 courses of the specialty “Pedagogy and psychology” of Abay Kazakh National Pedagogical University in order to identify knowledge about digital educational resources, MOOC. 94 students took part in the survey. It was found that students were poorly informed about MOOC, but expressed a desire to study digital courses. Key words: digital competence, develop a digital competence, open education, distance learning, massive open online courses.